The elusive primary: metastatic adenocarcinoma of the breast presenting solely as a hard sternal mass - Mohd Omar, Rozaliekah; Ismail, Ilham Ameera; Md Yasin, Mazapuspavina; Ahmad Affandi, Khairunisa; Husainy Hasbullah, Harissa; Mohamad Ali, Norliana Dalila (International Scientific Information, Inc., 2023)
Background: Carcinoma of unknown primary (CUP) is a diverse category of malignancies diagnosed in patients who have metastatic disease but without an identifiable primary tumor at initial presentation. Case Report: We report a case of CUP which was later diagnosed to be metastatic adenocarcinoma of the breast in a 62-yearold woman. The patient initially presented to a primary care clinic with an incidental finding of a small hard mass in the middle of the sternum, with no other clinical findings in the breast or axillary lymph nodes. Chest X-ray, ultrasound, and CT scan of the sternum suggested a benign sternal lesion, and a mammogram was normal. Due to the persistence of the mass, a biopsy was performed. The histopathological findings revealed a metastatic adenocarcinoma, most likely from breast origin, with positive estrogen receptor (ER) and mammaglobin on immunohistochemistry studies. The patient subsequently underwent PET scan, repeat mammogram, and MRI of the breast. Following high uptake in the rectum on PET, a colonoscopy was performed, revealing a suspicious rectal mass. The mass was surgically excised, and the final histopathological examination concluded the mass was a second primary adenocarcinoma of the rectum. Genetic analyses for BRCA1 and BRCA2 were negative. Conclusions: This is a rare case of an isolated bone-like lesion on the sternum due to metastatic adenocarcinoma of the breast in a patient with no prior history of breast cancer and lacking any clinical or radiological evidence of breast or axillary lymph node lesions on presentation. The patient was also subsequently diagnosed with 2 primary carcinomas. Thorough clinical examination, extensive radiological investigations, laboratory investigations, histopathological examination, and a multidisciplinary approach are essential in managing CUP.